Simulation of the stress distribution in diamond coatings applied by chemical vapor deposition on martensitic stainless steel X46Cr13 with a deterministic surface microstructure - Börner, Richard; Helmreich, Thomas; Göltz, Maximilian; Bandaru, Nithin Kumar; Steinert, Philipp; Schaarschmidt, Ingo; Rosiwal, Stefan; Schubert, Andreas (Thin Solid Films, 2025)
Abstract Diamond coatings are widely used in tribology for their exceptional mechanical, thermal, and chemical properties. Combining these advantages with the versatility of steel, the most common technical metal, presents challenges such as graphite formation, carbon diffusion, and residual stresses from thermal expansion mismatches during high-temperature coating processes. To address these, an intermediate layer is applied, and stress management techniques are employed. One method involves machining deterministic microstructures on the steel substrate using ultrasonic vibration superimposed machining. Polycrystalline diamond coatings are then applied to martensitic stainless steel X46Cr13 with a titanium nitride (TiN) intermediate layer using chemical vapor deposition as application technique for both coatings. Finite element analysis in Abaqus simulates stress generation during cooling, incorporating material data from dilatometer measurements. Simulations explore variations in diamond coating thickness, structural heights, and distances, assessing their impact on hydrostatic stresses. Results, validated by Raman measurements, reveal compressive residual stresses across all cases, with a maximum of -7 GPa on nearly flat surfaces and values closer to zero for rougher surfaces. This confirms that microstructured substrates significantly reduce residual stresses. The model is most accurate when the diamond coating thickness equals or is up to three times the structural heigh
Keywords: Diamond; Finite element analysis; Interlayer; Raman spectroscopy; Residual stresses; Simulation; SteelTitanium nitride; Thermal expansion; Ultrasonic vibration superimposed machining; X46Cr13